How to Help Female Victims of Domestic Violence? A Dialogue Between Scientific, Professional and Political Expert to Build Networks of Support - Piga, Maria Lucia (Italian Sociological Review, 2018)
How and through which instruments can social policies prevent domestic violence? Three of these instruments are, in our point of view: 1) the professional competence of the social workers and caregivers in protecting and preventing; 2) a shared gender-sensitive methodology, to help victims of domestic violence; 3) and the dialogue (necessary but not yet realized) among scientific, professional and political experts. Competent help is the pivot around which prevention strategies can be developed, to support networks of solidarity with victims. The building of networks is conclusive in overcoming the lack of social capital, above all in situations characterized by the fragility of social ties. Furthermore, the sector skill alliance could represent an innovation in the field of interventions to prevent the phenomenon of domestic violence and to build a more radical culture of non-violence in interpersonal relationships. In that way it will be possible a common vision on gender-based violence in diverse disciplinary fields: medicine, sociology, psychology, human rights, social services, criminology, social pedagogy and, at the same time, outline social policies that lead to effective solutions.